Evaluation of isavuconazole MIC strips for susceptibility testing of Aspergillus and Scedosporium species. (14th August 2018) - Trovato, L; Scalia, G; Palermo, C I; Costanzo, C M; Oliveri, S
Abstract: Isavuconazole is a new triazole with an expanded-spectrum and potent activity against moulds and yeasts. It has been authorized for use in adults for the treatment of invasive aspergillosis and for mucormycosis. The only commercially available isavuconazole susceptibility test is the minimum inhibitory concentration (MIC) strip isavuconazole test. The objective of this study was to assess the in vitro activity of isavuconazole using gradient concentration MIC strips, compared with the EUCAST broth microdilution reference method. A total of 147 clinically relevant fungal isolates comprising 120 Aspergillus sp. and 27 Scedosporium apiospermum complex were tested for susceptibility to isavuconazole using the EUCAST broth microdilution method and by the MIC strip isavuconazole test. The percent essential agreement between the two methods was calculated within a 1-fold dilution. The geometric means for the MICs using the EUCAST reference methods and the strip test were respectively: 0.60 mg/l and 0.65 mg/l for A. fumigatus, 0.70 mg/l and 0.77 mg/l for A. flavus, 1.50 mg/l and 1.25 mg/l for A. niger, 0.41 mg/l and 0.38 mg/l for A. terreus, 1.22 mg/l and 1.08 mg/l for S. apiospermum complex. The isavuconazole MIC strips showed good agreement with the EUCAST reference method. Isavuconazole MIC strips could be useful for susceptibility testing of Aspergillus sp. and S. apiospermum complex.